PSEUDO DEMOKRASI DALAM PERSPEKTIF KEADILAN BERMARTABAT - Rosita Risma Yanti, Rosita Risma Yanti; Afifah, Afifah; ‘Atiqoh, Layina Bayin; Abdulloh, Irbahuddin (SINDA: Comprehensive Journal of Islamic Social Studies, 2021)
Democracy in Indonesia is experiencing distortion because of the many things that are paradoxical to democracy, namely the Corruption Perception Index which is getting lower and is below the average of countries in the world. SOEs that are managed haphazardly and are only used as a place for compensation for political support so that they bear the burden of mega-debt and instead suck up state finances. And the regulations for the implementation of democracy are made only for the momentary interests of the ruling party and are unable to provide good democratic education to the people. In the perspective of dignified justice, democracy should be carried out with good intentions so that it can make Indonesian society a prosperous society. With the principle of ngewongne wong (humanizing humans) we should act as best we can for the benefit of others, especially for the primary interests of all our beloved Indonesian people. Dignified justice originating from divine values ​​as the upper stream and noble values ​​of society (volkgeist) idealizes an essential democracy that is properly implemented for the benefit of the people so that it can prosper all Indonesian citizens in particular and can make a significant contribution to human civilization.